Effects of palm kernel expeller and its oligosaccharides on nutrient assimilation and cecal microbiota in broiler chickens - Chen, Wei Li (2017)
The attempt to use palm kernel expeller (PKE) as an alternative feed ingredient in broiler chickens has encountered several constraints, including the adverse anti-nutritional effects of PKE on chicken performance caused by its high fiber content. One of the methods proposed to overcome this problem is the use of appropriate enzymes to hydrolyze the fiber component into more soluble sugars which presumably can then be used by the birds. However, studies have shown that enzyme treatment could successfully reduce the fiber contents but when the enzyme treated PKE was fed to the birds, results of birds’ performance were generally not encouraging and inconsistent. It has been hypothesized that the lack of improvement in animal performance when fed with enzyme-treated PKE is due to the poor assimilation of its enzymatic products, which are mainly consisted of mannose monomers. Apart from direct utilization of nutrient by the animal, gut microbiota were also known to help in harvesting nutrient from the feed and making them available to the host animal. In addition, the mannanoligosaccharides extracted from PKE (OligoPKE) have been reported to be a potential prebiotics owing to its ability in decreasing pathogenic bacteria and improving animal immune system. To date, the effects of PKE on mannose and other nutrient assimilation, changes in microbial diversities and functional properties that could possibly led to the lack of improvement in growth performance despite the increase in the nutritional value of PKE after enzyme treatment remain unclear. Thus, this thesis investigated the effects of supplementing enzyme-treated PKE on growth performance, specifically from the aspects of nutrient assimilation and the diversity and functional potential of cecal microbiome to fill the knowledge gap in this area. Concurrently, the prebiotic potential of OligoPKE was also evaluated.Results of this study showed that fermenting PKE at 60% initial moisture with 9.0 U/g PKE mannanase at 51°C for 18 h resulted in approximately 40% reduction in the crude fiber, 57% and 22% increase in monosaccharides and oligosaccharides, respectively. Broiler chickens fed with 5% and 20% enzyme-treated PKE, respectively, for starter and finisher periods had no detrimental effect (P>0.05) on the body weight gain, feed intake, and feed conversion ratio (FCR) as compared to control. However, no advantage in term of the above animal performance data was noted between enzyme treated and non-treated PKE. The capability of broilers to assimilate PKE-derived mannose and other nutrient was evaluated based on the disappearance of mannose from the intestinal tract (digestibility trial) and the expression of mannose absorption transporter (SGLT4). Results indicated that enzyme-treated PKE had significantly higher (P<0.05) apparent mannose digestibility as compared to untreated PKE. In addition, the expression of mannose transporter (SGLT4) was significantly increased (P < 0.05) in all the PKE-based diets, further suggesting that assimilation of mannose were efficient. Evaluation of the cecal microbiota using the 16S rRNA deep-sequencing analysis showed the replacement of the phylum Bacteroidetes by the phylum Firmicutes in Day-14 broiler and Day-28 broiler fed with treatment diets (untreated PKE, enzyme-treated PKE and OligoPKE). At both ages, the relative abundance of phylum Firmicutes were higher in the untreated PKE as compared to enzyme-treated PKE group, suggesting the higher efficiency of untreated PKE in enhancing cecal microbiota involved in increasing nutrient intake or nutrient absorption as compared to enzyme-treated PKE. In addition, the supplementation of OligoPKE showed to increase (P<0.05) the abundance of Lactobacillus, especially in the 14 day-old broiler chicks. In conclusion, results of the present study showed that despite the positive effect of such pre-treatment on reduction in fiber content, the non-effectiveness of enzyme-treated PKE in improving the growth performance of broiler chickens was not due to the poor assimilation of mannose sugars. Instead, it is possible that the above observation was a result of changes in the cecal microbiota, in which untreated PKE was able to support bacteria involved in increasing nutrient intake, whilst enzyme-treated PKE stimulated growth of group of bacteria that often relates to decrease in nutrient intake.